Drought Response Mechanisms and Adaptation: An Analysis of Strategies Adopted by Wine Grape Farmers in the Western Cape - Riedo, Giulia (Department of Environmental and Geographical Science, 2020)
This thesis examines the response mechanisms and adaptation strategies adopted by grapevine farmers to counteract the effects of the 2015-2018 Western Cape drought, which was characterised as particularly rare and severe. The challenges that emerged during the drought within the study area were exacerbated by the increasing competition over water resources between urban and agriculture users, as investment to supply water to urban users are expected to bring more economic and social value than investments in water supply for agriculture. The study responds to the dearth of literature on climate change adaptation strategies by grapevine farmers in South Africa. Using information from 27 open-ended, face to face interviews conducted with grapevine farmers operating in the Berg River catchment area, as well as an analysis of existing economic and weather data, the research sought to understand the effects of the water stress on grapevine production, the main cause of yield loss and the key drivers of farmers’ behaviour shifts. Analysis of industry production performance from 2015 to 2018 and observed rainfall from 2015 to 2017 suggests that water stress remains the key factor influencing grapevine yields. The water stress was also found to have catalysed later ripening of red varieties, higher pH levels in the wine and the introduction of emergency pruning methods to reduce water use, which in turn led to uneven budding budding due to pruning methods, later ripening of red varieties, higher pH levels in the wine. It was also found that the depleting quality of the Berg River water led to reduced yield, as well as heightened financial and psychological stress. The research identifies a portfolio of long-term and short-term adaptation options pursued by farmers in the study area, entailing reduced water consumption and increased water efficiency. The research identified that the drought induced farmers to suspend or reduce plant replacement. However, this behavior cannot be explained simply as responses to climate change, but that this is linked to the low profitability of the local wine grape industry. Most farmers adopted incremental measures rather than transformative strategies, where the major barriers to transformative adaptation included uncertainty regarding climate trends, limited financial capacity for large investments, the belief in grapevine drought resilience and the cultural attachment to viticulture.